Still life - a novel and reflexive essay - Myburgh, Pier (My University, 2008)
ABSTRACT The largest part of this thesis is a novel called Still Life, which explores the mourning process of a mother who loses her baby, and the effect it has on her life and her marriage. The novel alternates between the present and the past (which is 23 years before) so that it illustrates the mother’s reaction to the death of her baby at the time of the death, and her personal development (or lack thereof) many years on.The second part of the thesis is an essay, which reflects on grieving in general and the expression of grief through literature, as well as some of the aspects of the writing process, with particular consideration given to the development of plot,the choice of point-of-view, symbolism, the ending and the choice of writing in a second language.
Keywords: novel; death; baby; mourning; grief; relationships; plot; point-of-view